2009
DOI: 10.1002/chem.200900457
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of an Intramolecular Hydrogen‐Evolving Ru–Pd Photocatalyst

Abstract: Photoinduced electron-transfer processes within a precatalyst for intramolecular hydrogen evolution [(tbbpy)(2)Ru(tpphz)PdCl(2)](2+) (RuPd; tbbpy = 4,4'-di-tert-butyl-2,2'-bipyridine, tpphz = tetrapyrido[3,2-a:2',3'c:3'',2'',-h:2''',3'''-j]phenazine) have been studied by resonance Raman and ultrafast time-resolved absorption spectroscopy. By comparing the photophysics of the [(tbbpy)(2)Ru(tpphz)](2+) subunit Ru with that of the supramolecular catalyst RuPd, the individual electron-transfer steps are assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
174
0
13

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 134 publications
(204 citation statements)
references
References 59 publications
7
174
0
13
Order By: Relevance
“…This behavior is in agreement with the closely related species 1 and 2 in which as tepwise photoinduced electron transfer from the ruthenium photocenter to the catalytically active palladium or platinum center is observed (Figure 1). [20,32,33] This observation indicates that the ultrafast photoinduced electron-transfer processes are not affected by the exchange of the terminal Pt bound anions.W etherefore considered the potential changes in the catalytic mechanism occurring at the platinum center.The kinetic processes during the light-driven hydrogen production of the photocatalysts 2 and 3 were compared. In spite of the fact that 3 shows as ignificantly increased catalytic activity its underlying photocatalytic behavior is in line with that observed for 2.I mportantly, both catalysts show an instant hydrogen formation and arelatively constant TOFuntil the maximum TONisreached (catalytic activity of 3 is shown in Figure 2).…”
mentioning
confidence: 84%
“…This behavior is in agreement with the closely related species 1 and 2 in which as tepwise photoinduced electron transfer from the ruthenium photocenter to the catalytically active palladium or platinum center is observed (Figure 1). [20,32,33] This observation indicates that the ultrafast photoinduced electron-transfer processes are not affected by the exchange of the terminal Pt bound anions.W etherefore considered the potential changes in the catalytic mechanism occurring at the platinum center.The kinetic processes during the light-driven hydrogen production of the photocatalysts 2 and 3 were compared. In spite of the fact that 3 shows as ignificantly increased catalytic activity its underlying photocatalytic behavior is in line with that observed for 2.I mportantly, both catalysts show an instant hydrogen formation and arelatively constant TOFuntil the maximum TONisreached (catalytic activity of 3 is shown in Figure 2).…”
mentioning
confidence: 84%
“…This absorption wavelength is almost identical to that of the unsubstituted dinuclear Ru(tpphz)PdCl 2 , which has a maximum at 444 nm attributed to the population of the 1 MLCT state. 31 However, the extinction of Ru(bmptpphz)PdCl at 447 nm (ε = 39 × 10 3 M −1 cm −1 ) is almost twice as high as the extinction of Ru(tpphz)PdCl 2 at 444 nm (ε = 20 × 10 3 M −1 cm −1 ), indicating that the enhanced absorption of visible light due to the novel substitution pattern of the bridging ligand is also maintained for the dinuclear complex. As mentioned above, the main absorption band in the visible range is shifted from 414 nm (Ru(bmptpphz)) to 447 nm (Ru(bmptpphz)PdCl) (see ESI …”
Section: Synthesis and Characterizationmentioning
confidence: 98%
“…As typically found for hetero bimetallic ruthenium tpphz complexes, the second metal centre induces a MLCT phen → MLCT pz relaxation, which leads to a dominant population of a low-energy "dark state" located on the phenazine part, and so causes the decrease of the emission intensity and the bathochromic shift of the emission maximum. 31,44,45 Electrochemical properties Cyclic voltammetry was used to obtain the redox potentials of Ru(bmptpphz) and Ru(tpphz) in acetonitrile ( Table 2). Analogously to Ru(tpphz), Ru(bmptpphz) shows the metal based oxidation wave at 0.82 V and multiple waves assignable to ligand based reductions, which are attributed to the reduction of the phenazine part (−1.44 V) and the ruthenium bound phen part of tpphz (−2.27 V), as well as to the first and second reduction of the terminal tbbpy ligands (−1.90, −2.10, and −2.44, −2.90 V).…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…Route (ii) can be taken by screening properties of the catalytic system like solvent composition, pH value and ionic additives. 5,7,[23][24][25][26][27] Within this research, it has, for instance, been shown that the addition of N(C 4 H 9 ) 4 Cl to the photocatalytic system for the light induced formation of hydrogen from water based on [Ru(tbbpy) 2 (tpphz)-PdCl 2 ](PF 6 ) 2 (RutpphzPd) (ruthenium(II)-bis(4,4′-di-tert-butyl-2,2′-bipyridyl)-(μ-tetrapyrido[3,2-a:2′,3′-c:3″,2″-h:2′″,3′″-j]phenazine)-(dichloropalladium)-dihexafluorophosphate) ( Fig. 1) leads to a significant drop in catalytic activity.…”
Section: Introductionmentioning
confidence: 99%